2022
DOI: 10.1002/adhm.202102682
|View full text |Cite
|
Sign up to set email alerts
|

Au@Ag Nanorods‐PDMS Wearable Mouthguard as a Visualized Detection Platform for Screening Dental Caries and Periodontal Diseases

Abstract: The development of easy-to-use, low-cost, and visualized detection platforms for screening human dental caries and periodontal diseases is in urgent demand. In this work, a Au@Ag nanorods-poly(dimethylsiloxane) (Au@Ag NRs-PDMS) wearable mouthguard, which can visualize the tooth lesion sites through the color change of it at the corresponding locations, is presented. The Au@Ag NRs-PDMS composite exhibits a distinct color response to hydrogen sulfide (H 2 S) gas generated by bacterial decay at the lesion sites. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Studies have shown the availability of oral wearable devices for various applications, including caries detection, force measurement on orthodontic teeth, detection of implant abnormalities, and assessment of salivary biochemical indicators. 29 , 30 , 31 , 32 While the majority of these studies are still in the laboratory phase, these devices are likely to be used in future to collect data to enhance people’s lifestyle choices and oral health practices. These collected data could be sent to dental professionals for effective patient management.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown the availability of oral wearable devices for various applications, including caries detection, force measurement on orthodontic teeth, detection of implant abnormalities, and assessment of salivary biochemical indicators. 29 , 30 , 31 , 32 While the majority of these studies are still in the laboratory phase, these devices are likely to be used in future to collect data to enhance people’s lifestyle choices and oral health practices. These collected data could be sent to dental professionals for effective patient management.…”
Section: Discussionmentioning
confidence: 99%
“…The mouthguard biosensor exhibits high sensitivity and selectivity toward uric acid in human saliva, which can be used to monitor the health condition of hyperuricemia patients. Other biomarkers such as glucose, thiocyanate, H2S gas, and N-epsilon (carboxymethyl) lysine also can be detected using the same technology [122][123][124][125]. Various forms of wearable sensors have been designed to achieve real-time monitoring purposes such as patch type, fabric type, and tattoo type [126][127][128][129].…”
Section: Mouthguard Sensorsmentioning
confidence: 99%
“…The mouthguard biosensor exhibits high sensitivity and selectivity toward uric acid in human saliva, which can be used to monitor the health condition of hyperuricemia patients. Other biomarkers such as glucose, thiocyanate, H 2 S gas, and N-epsilon (carboxymethyl) lysine also can be detected using the same technology [ 122 , 123 , 124 , 125 ].…”
Section: Application Mannersmentioning
confidence: 99%